Curating culture: Instagram and the visual representation of heritage tourism in Surabaya - Aulia Rahmawati; Ririn Tutiasri; Syafrida Febriyanti (Faculty of Communications Science, Dr. Soetomo University, 2024)
This study investigates how Instagram shapes public engagement with cultural heritage through a case study in Surabaya, Indonesia. Surabaya possesses diverse assets; however, its tourism potential remains underexplored compared with established destinations such as Yogyakarta. Instagram offers opportunities to study how Surabaya’s identity is visually constructed and promoted to visitors. Through hashtag #surabayaheritage, users practice certain perspectives on the city’s multifaceted history. This study aims to investigate how Instagram shapes public engagement with cultural heritage through a case study of Surabaya, Indonesia. Specifically, this research examines how Surabaya's identity is visually constructed through the hashtag #surabayaheritage on Instagram. Employing both qualitative content analysis and critical visual discourse, this study examined 100 top Instagram posts, revealing that heritage discourse dominated the posts, with Dutch colonial buildings being the primary photographic subjects. The research findings also emphasise that while the historical discourse emphasises architectural details and educational history, it marginalises other aspects of cultural heritage, especially those that do not originate from the colonial era. By applying visual discourse analysis, this aestheticised selective gaze indicates the productive power of Instagram conventions in framing heritage sites. Further research should incorporate non-Instagram perspectives and spatial analysis. As heritage tourism expands globally, critical examination of social media discourse provides vital insights into the risks and opportunities for inclusive and sustainable development, particularly for local communities.